43-59 Fenomena Pluralisme Agama Dan Budaya Di Indonesia Sebagai Wujud Implementasi Pancasila Sila Ke 3 - Khomarudin Gilang Ramadhan; Naurah Tania Putri; Erwin Kusumastuti (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2022)
In our country Indonesia there is a state ideology, one of which is the unity of Indonesia which is in the 3rd precept, here we have the right to choose and determine freedom of religion, in Indonesia there are 6 recognized religions namely Islam, Christianity, Hinduism, Buddhism, Catholicism, Konghuchu. In addition, in Indonesia there are thousands of islands and certainly have various cultures and traditions that become typical cirri of the area Differences in religious diversity on the one hand cause divisions among people. This difference on the one hand causes divisions between peoples and people who can trigger national dicentration, in Islamic teachings we are taught mutual tolerance for all aspects, especially to religious people. Tolerance is shown to one of Allah's messengers, the Prophet Muhammad (peace be upon him), with his love and patience for his people the Apostle is able to spread islam in a peaceful way without disturbing the belief of islam in a peaceful way without disturbing the beliefs of others. Indonesia with its plurality has major challenges, especially in religious differences, because Indonesia tends to be vulnerable to the division of religious people that should be able to support the sovereignty of the nation and state. Di negara kita Indonesia terdapat ideologi negara yang salah satunya adalah persatuan indonesia yang berada di sila ke 3, disini kita berhak memilih dan menentukan kebebasan beragama, di Indonesia terdapat 6 agama yang diakui yaitu islam, kristen, hindu, budha, katholik, konghuchu. Selain itu di Indonesia terdapat ribuan pulau dan pastinya memiliki macam-macam kebudayaan dan tradisi yang menjadi cirri khas dari daerah tersebut Perbedaan keberagaman agama disatu sisi menyebabkan perpecahan antar kalangan umat bergama. Perbedaan ini disatu sisi menyebabkan perpecahan antar kalangan masyarakat dan umat bergama yang dapat memicu disentrigasi nasional, didalam ajaran islam kita diajarkan saling toleransi untuk segala aspek terlebih lagi kepada umat beragama. Sikap toleransi di tunjukan kepada salah satu utusan Allah SWT yaitu nabi Muhammad SAW, dengan rasa cintanya dan sabarnya kepada umatnya Rasullulah mampu untuk menyebarkan agama Islam dengan cara damai tanpa mengganggu kepercayaan agam lain. Indonesia dengan kemajemukannya memliki tantangan besar terutama dalam perbedaan agama, karena Indonesia cenderung rentan dengan perpecahan umat beragama yang seharusya perbedaan itu dapat menompang kedaulatan bangsa dan negara.